The Economic Impact and Cost of Visual Impairment due to Cataract in West Nusa Tenggara Province - Effendi, Raden Gunawan; Setyowati, Ety Retno (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
Blindness and severe visual impairment have a significant impact on quality of life (QOL). This leads to reduced productivity and economic burden for Indonesia. The economic valuation of visual impairment is an important tool for making recommendations and making cost-sharing decisions. Using a cost-benefit analysis (CUA) approach, this study estimates the economic impact of blindness and severe visual impairment, and describes the value of cataract surgery in Indonesia. The aim of this study was to estimate the economic losses due to blindness and severe visual impairment and to describe the cost-benefit analysis of cataract surgery in Indonesia. Prevalence data were collected from Indonesia’s Rapid Assessment of Avoidable Blindness (RAAB) survey from 2014 to 2016 and the cost of cataract surgery was averaged across the system. Indonesian case base groups system (INA-CBGs) was approved on the basis of reasonable national surgical costs. The economic evaluation is described using a cost-benefit analysis approach per quality-adjusted life years (QALYs). The following results: The number of QALYs lost to blindness and severe visual impairment in Indonesia is approximately 84,866 QALY and 49,440 QALY, respectively. The total economic loss was 3.38 trillion IDR in a year and is expected to increase to 24.41 IDR trillion in 5 years. As a highly cost-effective procedure, cataract surgery brings about 79,564 QALY profit or economic benefit worth 2.0 trillion IDR for Indonesia.